2008
DOI: 10.1159/000164684
|View full text |Cite
|
Sign up to set email alerts
|

Australian Study on Public Knowledge of Human Genetics and Health

Abstract: Aims: This study was designed to obtain data on public understanding of genetic concepts in the adult population of Western Australia. It explored knowledge of genetic risk of disease, inheritance, biology, determinism, and factors that predict relatively higher genetic knowledge within the general population. Method: A cross-sectional telephone survey of 1,009 respondents. Results: Most members of the Western Australian community are aware of basic genetic concepts and the link between genes, inheritance, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
148
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(172 citation statements)
references
References 46 publications
(71 reference statements)
21
148
3
Order By: Relevance
“…38 There is also a growing need to improve public and professional knowledge of genomics and, now, personalized medicine. [39][40][41][42][43] Although these educational needs certainly existed before the emergence of personalized medicine, it is hoped that the increasing interest in the translation of personalized medicine tests and technologies will renew efforts to increase public and professional discourse of the benefits and risks of personalized genomic tests that aim to stratify patients and inform treatment decision making, and not ration health care.…”
Section: Discussionmentioning
confidence: 99%
“…38 There is also a growing need to improve public and professional knowledge of genomics and, now, personalized medicine. [39][40][41][42][43] Although these educational needs certainly existed before the emergence of personalized medicine, it is hoped that the increasing interest in the translation of personalized medicine tests and technologies will renew efforts to increase public and professional discourse of the benefits and risks of personalized genomic tests that aim to stratify patients and inform treatment decision making, and not ration health care.…”
Section: Discussionmentioning
confidence: 99%
“…13,16 Men seem to have more positive attitudes towards testing, 10,13 but some studies have indicated that women are more knowledgeable on genetics. 17,18 Higher levels of genetic knowledge, mostly among those with higher education, are associated with a more favourable attitude towards genetics in some studies, 16,19 but this association was not found in others. 10,13 The relationship between knowledge and support of testing seems more complex, because more knowledge may translate to a less perceived benefit of testing.…”
Section: Introductionmentioning
confidence: 94%
“…Erby, Roter, Larson, & Cho, 2008;Hooker et al, 2014;Hott et al, 2002;Molster, Charles, Samanek, & O'Leary, 2008;Pearson & Liu-Thompkins, 2012;Saul, 2013). They have also largely focused on well-defined populations such as undergraduate students and young adults (Carver et al, 2017;Fitzgerald-Butt et al, 2016).…”
Section: Problem Statementmentioning
confidence: 99%
“…For example, in one study participants were asked to classify various traits and health conditions (e.g. eye colour, cystic fibrosis, heart disease) as being either entirely genetic, entirely environmental or a mixture of both (Molster et al, 2008). However, it was not thought appropriate to use such a restricted measure for the traits of interest in iGLAS, as research has consistently shown that all complex human traits are a combination of genes and environments (Collins, 2010;Plomin et al, 2016).…”
Section: Heritability Estimatesmentioning
confidence: 99%